PROSES KREATIF MEMBANGUN STRUKTUR NARATIF DALAM FILM DOKUMENTER OBSERVASIONAL œPADU AREP - Putra, I Made Denny Chrisna; Pamungkas, Epriliana Fitri Ayu; Bumiarta, Made Rai Budaya (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2023)
Gending rare or sekar rare in Bali represents a form of singing that parents traditionally perform for their children. The ever-expanding influence of globalization, ushering in new cultural trends that often transform into popular culture, has consistently overshadowed indigenous cultures, including that of gending rare. It is imperative to undertake preservation efforts through appropriate means before traditional cultures and artistic expressions become marginalized amidst the tidal wave of popular culture. One effective avenue for cultural preservation is the creation of observational-style documentary films. As a medium for preservation, documentary films should be meticulously crafted, not only to engage the audience but also to adhere to a coherent narrative structure. The objective of this endeavor is to unveil the creative process involved in constructing a narrative framework within the context of an observational-style documentary, titled